2022
DOI: 10.21037/tlcr-22-162
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment line on risks and benefits of immune checkpoint inhibitor in patients with advanced non-small cell lung cancer and interstitial lung disease: a systematic review and meta-analysis of cohort studies

Abstract: Background: There is no clear consensus regarding the safety and efficacy of immune checkpoint inhibitors (ICIs) in patients with advanced non-small cell lung cancer (NSCLC) and pre-existing interstitial lung disease (ILD). We aimed to elucidate the impact of ICIs on pre-existing ILD. Methods:We systematically queried PubMed-MEDLINE, Embase-Scopus, and ISI Web of Science databases up to January 10, 2022. The pooled any-grade and grade 3-5 ICI-associated pneumonitis (ICIP) rate and objective response rate (ORR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The incidence of CIP in NSCLC patients with ILD has been analyzed in predominately retrospective studies and reported to be 11.1-42.9%, which is higher than in those without ILD (5.8-11.6%) (108-116) (Table 7). Recent meta-analyses of ICI therapy also found a significantly higher incidence of any grade and grade ≥ 3 pneumonitis in NSCLC patients with ILD, especially IPF, than in those without ILD (107,117). Accumulating evidence suggests risk factors other than pre-existing IPF for CIP include patients aged > 70 years old (118) ; those with Eastern Cooperative Oncology Group performance status score 2 or higher (119) ; comorbid lung diseases, such as asthma and chronic obstructive pulmonary disease (120) ; pre-existing interstitial lung abnormalities on baseline chest computed tomography (112) ; decreased FVC (121) ; prior thoracic radiotherapy (120) ; squamous cell lung carcinoma (122) ; and combination ICI therapy (123).…”
Section: The Effect Of Icis For Lc-ildmentioning
confidence: 99%
“…The incidence of CIP in NSCLC patients with ILD has been analyzed in predominately retrospective studies and reported to be 11.1-42.9%, which is higher than in those without ILD (5.8-11.6%) (108-116) (Table 7). Recent meta-analyses of ICI therapy also found a significantly higher incidence of any grade and grade ≥ 3 pneumonitis in NSCLC patients with ILD, especially IPF, than in those without ILD (107,117). Accumulating evidence suggests risk factors other than pre-existing IPF for CIP include patients aged > 70 years old (118) ; those with Eastern Cooperative Oncology Group performance status score 2 or higher (119) ; comorbid lung diseases, such as asthma and chronic obstructive pulmonary disease (120) ; pre-existing interstitial lung abnormalities on baseline chest computed tomography (112) ; decreased FVC (121) ; prior thoracic radiotherapy (120) ; squamous cell lung carcinoma (122) ; and combination ICI therapy (123).…”
Section: The Effect Of Icis For Lc-ildmentioning
confidence: 99%
“…Taxane-containing chemotherapy, targeted therapies such as epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs), and immune checkpoint inhibitors (ICIs) are common causes of drug-induced ILDs during systemic LC therapies [ 14 16 ]. Although targeted therapies and immunotherapy have significantly improved the prognosis of advanced LCs, patients with pre-existing ILD should be treated cautiously because of the increased risk of treatment-induced ILD [ 17 , 18 ]. Baseline ILD was considered a relative contraindication to ICI therapy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%